2021
DOI: 10.1080/0907676x.2021.1892785
|View full text |Cite
|
Sign up to set email alerts
|

Fight for focus: attention and agency in sight-translated interaction

Abstract: This paper presents an analysis of three roleplayed interpreted institutional meetings in which sight translation is part of the interaction. The analysis is based on multimodal (inter)action analysis and utilises the analytical tool of modal density as indication of attention/awareness. This analytical framework is novel in interpreting studies. The data include filmed material from an experimental setting and participants' reflections about the situation. The findings show variations in sight translation pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Kaindl, 2012Kaindl, , 2020 and lately also in interpreting studies focusing on hybrid forms such as, for example, sight interpreting (e.g. Havnen, 2019Havnen, , 2022, speech-to-text captioning (e.g. Platter, 2019) or subtitling through respeaking (e.g.…”
Section: Interpreting During Wiretapping: a Hybrid Translational Acti...mentioning
confidence: 99%
“…Kaindl, 2012Kaindl, , 2020 and lately also in interpreting studies focusing on hybrid forms such as, for example, sight interpreting (e.g. Havnen, 2019Havnen, , 2022, speech-to-text captioning (e.g. Platter, 2019) or subtitling through respeaking (e.g.…”
Section: Interpreting During Wiretapping: a Hybrid Translational Acti...mentioning
confidence: 99%
“…The use of resources in the translation and interpreting process is related to information behaviour, which is defined as all behaviours related to information people receive and exchange, including media use and all the communication activities between people (Jiang, 2019). Previous studies related to information behaviour examine the search strategy used in the translation process (Whyatt, Witczak, & Tomczak, 2021), the behaviours of students and professional translators in web searching (Ohnishi & Yamada, 2020), the interaction between translator and computer (Bundgaard, 2017), and between translator/interpreter and information (Havnen, 2021). It may be concluded that research on this particular topic has become more pragmatic, focusing on problem-solving for technology development, time efficiency, and high quality to meet the global market demand.…”
Section: Introductionmentioning
confidence: 99%
“…Thawabteh, 2009). A pedagogical study of discussion interpreting emphasizes the urgent of the interpreter need to involving and not involving interlocutors; this idea is also true with the foreign langue learners' consideration in the instructional process (Arbain, 2020;Havnen, 2021;Maulana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%